Co-occurrence of Noonan and Cardiofaciocutaneous Syndrome Features in a Patient with KRAS Variant - Rodríguez, Fernando; Vallejos, Carla; Bolanos-Garcia, Víctor M.; Ponce, Diana; Unanue, Nancy; Garay, Francisco; Cassorla, Fernando; Aracena, Mariana (Journal of Pediatric Genetics, 2018)
We report the case of a 3-year-old girl, who is the third child of nonconsanguineous parents, with short stature, hypertrophic cardiomyopathy, and mild dysmorphic features; all suggestive of Noonan syndrome. In addition, the patient presents with feeding difficulties, deep palmar and plantar creases, sparse hair, and delayed psychomotor and language development, all characteristics frequently observed in cardiofaciocutaneous syndrome. Molecular analysis of the Ras/ MAPK pathway genes using high-resolution melting curve analysis and gene sequencing revealed a de novo KRAS amino acid substitution of leucine to tryptophan at codon 53 (p.L53W). This substitution was recently described in an Iranian patient with Noonan syndrome. The findings described in this report expand the phenotypic heterogeneity observed in RASopathy patients harboring a KRAS substitution, and advocate for the inclusion of genes with low mutational frequency in genetic screening protocols for Noonan syndrome and other RASopathies.
Keywords: Noonan syndrome; cardiofaciocutaneous syndrome; KRAS mutations